Chaperone-directed ubiquitylation maintains proteostasis at the expense of longevity. Issue 2 (3rd April 2017) - Pokrzywa, Wojciech; Lorenz, Robin; Hoppe, Thorsten
ABSTRACT: The integrity of the cellular proteome is supported by quality control networks, which govern protein synthesis, folding, and degradation. It is generally accepted that an age-related decline in protein homeostasis (proteostasis) contributes to protein aggregation diseases. However, the mechanistic principles underlying proteostasis imbalance and the impact on life expectancy are not well understood. We recently demonstrated that this interrelation is affected by chaperone-directed ubiquitylation, shifting the amount of the conserved DAF-2/insulin receptor both in Caenorhabditis elegans and Drosophila melanogaster . The ubiquitin ligase CHIP either targets the membrane bound insulin receptor or misfolded proteins for degradation, which depends on the cellular proteostasis status. Increased proteotoxicity triggers chaperone-assisted redirection of CHIP toward protein aggregates, limiting its capacity to degrade the insulin receptor and prevent premature aging. In light of these findings, we discuss a new concept for understanding the impact of proteome imbalance on longevity risk.